Eco-Consciousness, Treasure Hunting, Quality, and Attitude: Keys to Branded Thrifting Consumption - Iliyyin, Al Haqqul Ala; Kuswati, Rini (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze how eco-consciousness, treasure hunting, and product quality on purchase intention mediated by attitude on branded thrift products. Environmental awareness and the popularity of branded secondhand goods are important to understand the factors driving purchasing decisions. Methodology: This research methodology uses a quantitative survey approach. Purposive sampling was used to choose university students from all throughout Indonesia for the research sample. Questionnaires were used to gather primary data. Data analysis used Structural Equation Modeling (SEM) to test the hypothesis. Results: The results show that Eco-consciousness, Treasure Hunting, and Product Quality have a positive and significant effect on attitude. Attitude has a positive and significant effect on purchase intention. The results of the mediation test show that attitude significantly mediates the influence of eco-consciousness, treasure hunting, and product quality on purchase intention.Applications/Originality/Value: These findings provide practical implications for thrift business actors to increase consumer purchase intention by building a positive attitude. This can emphasize aspects of eco-consciousness, treasure hunting, and quality products.